Switchable dual band equilateral triangular microstrip patch antenna using pin diode. Issue 1 (7th April 2015) - Pratap, Prabal; Bhatia, Ravinder Singh; Kumar, Binod
Abstract : Purpose: – The purpose of this paper is to study and calculate the electrical characteristic of an equilateral triangular microstrip patch antenna that is proposed for dual frequency operation using the pin diode. The electrical characteristic of an equilateral triangular microstrip patch antenna is proposed for dual-frequency operation. Spur lines and ON/OFF condition of the pin diode are utilized to switch the resonant frequency of the patch. The presence of spur lines excites the surface current of the patch which is dependent on the resonant frequency of an equilateral triangular microstrip patch. Insertion of the diode in the spur lines gives a better result and compactness in patch design, which improves the miniaturization in size of patch. Design/methodology/approach: – Antenna Design Aspects: A basic structure of an equilateral triangular microstrip antenna (ETMA) having two spur lines and one pin diode positioned in between the spur line is considered in this paper. The design parameters are chosen on the basis of substrate materials having relative permittivity less than three. Specification of the antenna is given in Table I. Substrate material used is RT Duroid 5, 880; relative permittivity of the substrate er is 2.2; thickness of dielectric substrate h is 1.5 mm; sides of equilateral triangular patch a are 10 mm, spur width s is 0.5 mm; and spur length b is 2.0 mm. Findings: – This paper gives an account of achieving polarization swiftness with coplanar waveguide (CPW) feed. The miniaturized size of the antenna is 35 × 30 mm2. Switchable microstrip equilateral triangular antenna has been demonstrated for dual-frequency operations. The resonant frequency of an ETMA can be adjusted by setting the diode in an ON and OFF state. The design improves the miniaturization in size with a discussion of radiation density. The excited patch surface current is limited to flow around just the mid of the patch in simple ETMA with a single slit cut. It is observed that for an ETMA, when the diode is in the ON state at 9.16 GHz, the excited patch surface current is highly distributed in the patch compared to when the diode is in the ON state at 11 GHz. Similarly, it is observed that the excited surface patch current is highly distributed when the diode is in the OFF state in both frequencies (9 and 11.96 GHz). The mode is changed by the use of a switch at time and it is suitable for wireless communication applications. Originality/value: – Spur lines and the ON/OFF condition of the pin diode are utilized to switch the resonant frequency of the patch. The presence of spur lines excites the surface current of the patch which is dependent on the resonant frequency of an equilateral triangular microstrip patch. Insertion of the diode in spur lines gives a better result and compactness in patch design, which improves the miniaturization in size of the patch.